Peran Transformasi Hukum Pidana dalam Mengatasi Kejahatan Siber Berbasis AI dan Geopolitik - Richard, Richard; Andri, Andri; Tiawarman K., Andriansyah; Bombang Sapan, Heber (Pascasarjana UDA, 2025)
The development of artificial intelligence (AI) technology has had a major impact on the dynamics of cybercrime, which is increasingly complex and diverse. AI-based cybercrime, such as automated attacks, deepfakes, and data manipulation, creates new challenges in the global criminal law system. On the other hand, the growing geopolitical dynamics also influence law enforcement efforts against international cybercrime. This study aims to examine the role of criminal law transformation in addressing AI-based cybercrime in the context of ever-changing geopolitics. Using a normative juridical approach, this study identifies the main challenges in law enforcement, including issues of jurisdiction, international cooperation, and differences in geopolitical interests between countries. In addition, this study also proposes updating more adaptive criminal law regulations, increasing international cooperation, and strengthening the capacity of developing countries in dealing with AI-based cyber threats. It is hoped that the results of this study can contribute to the formulation of more effective policies in dealing with AI-based cybercrime globally.